Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fpsyg.2019.00424
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effect of Trait Emotional Intelligence Between the Behavioral Activation System (BAS)/Behavioral Inhibition System (BIS) and Positive and Negative Affect

Abstract: Gray (1970, 1981, 1987) proposed a behavioral motivation theory (Reinforcement Sensitivity Theory, RST), which describes the Behavioral Activation/Approach System (BAS) and the Behavioral Inhibition System (BIS). Some studies relate higher activation of BAS to positive affect, whereas BIS activation is linked to negative affect, particularly to high levels of anxiety and depression. Research data suggests that greater Trait Emotional Intelligence (TEI) influences optimal development of well-being and psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 44 publications
4
35
0
1
Order By: Relevance
“…16 Second, we found that high BAS sensitivity leads to lower levels of depression and anxiety and enhanced adaptive cognitive emotion regulation strategies. These findings are in line with those of previous studies reporting that BAS sensitivity is negatively associated with negative affect 24 and can positively predict adaptive cognitive emotion regulation. 23 BAS drives elderly adults to achieve goals, leading to effective implementation of adaptive strategies and a feeling of enjoyment when they attain them.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…16 Second, we found that high BAS sensitivity leads to lower levels of depression and anxiety and enhanced adaptive cognitive emotion regulation strategies. These findings are in line with those of previous studies reporting that BAS sensitivity is negatively associated with negative affect 24 and can positively predict adaptive cognitive emotion regulation. 23 BAS drives elderly adults to achieve goals, leading to effective implementation of adaptive strategies and a feeling of enjoyment when they attain them.…”
Section: Discussionsupporting
confidence: 93%
“…23 Similarly, people with high BAS scores are more likely to regulate their emotions and behaviors effectively. 24,25 Meanwhile, low BAS sensitivity and high BIS sensitivity are related to emotion regulation difficulties. 26 However, this preexisting literature on the association between BIS/BAS sensitivity and negative affect has mostly focused on certain emotion regulation strategies or emotion regulation difficulties, 27 while the cognitive emotion regulation which consist of adaptive and maladaptive strategies seems to be strongly linked to depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effectiveness of psychological interventions or therapeutic practices with a high attentional component, such as emotional consciousness or mindfulness, must be reviewed (Cebolla et al, 2017). In other words, emotional regulation and strengthening after adversity will be affected if emotional attention is not accompanied by an adequate ability to discriminate emotional states (Cejudo et al, 2016;Merchán-Clavellino et al, 2019. Thus, if interventions aim to promote adjustment and psychological well-being, the dimensions of PEI should work complementary to avoid unwanted effects.…”
Section: Discussionmentioning
confidence: 99%
“…There is even empirical evidence that certain therapeutic practices with an attentional component such as meditation and mindfulness can generate side effects that should be studied in greater depth (Cebolla et al, 2017). Nevertheless, if the attention is accompanied by the ability to discriminate and repair negative mood, these negative consequences are reduced, leading to better physical and psychological function (Cejudo et al, 2016;Gómez-Baya and Mendoza, 2018;Merchán-Clavellino et al, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Gray (1987) proposed a behavioral motivation theory (Reinforcement Sensitivity Theory [RST]), which describes the behavioral approach system (BAS) and the behavioral inhibition system (BIS). BAS refers to one's sensitivity to rewards and positive stimuli, activating behaviors that produce positive or pleasurable goals, whereas BIS refers to one's sensitivity to punishment cues and negative stimuli, inhibiting behaviors that produce unpleasant outcomes to avoid them (Carver & White, 1994;Merchán-Clavellino et al, 2019). Spielberg et al (2011) found that the activation approach (BAS, or approach motivation) was associated with left-lateralized middle frontal gyrus activation and that the region responds to stimuli associated with expectations, harvests, and pleasure.…”
Section: Approach and Avoidance Motivationmentioning
confidence: 99%